Model Penilaian Kesiapan KRI Kelas RE. Martadinata Berbasis Sistem Dinamik (Studi Kasus KRI REM - 331) - Sondra, William Alex; Dewi Puspaningtyas Faeni (LPPM Akademi Manajemen Administrasi Yogyakarta, 2025)
To support Indonesia’s vision as a global maritime axis, this paper analyzes theoperational readiness of the KRI R.E. Martadinata-class frigate (KRI REM-331).Utilizing a dynamic system model with a 25-year time horizon, the study evaluatesthe complex interactions between four key variables: Technical, Personnel,Logistics, and Combat Readiness. Simulation results indicate that focusing onTechnical Readiness alone increases overall readiness by an average of 3.7%,while prioritizing Logistics Readiness yields a 2.1% increase. A combined scenarioimproving both Technical and Logistics variables proved most effective, causingan average readiness increase of 5.5%. The study, therefore, concludes that whileTechnical Readiness is the single most influential variable, the most impactfulstrategy for significantly enhancing KRI readiness involves an integrated approachthat simultaneously advances both technical and logistical capabilities, therebystrengthening national maritime defense.